Development of a PET/Cerenkov‐light hybrid imaging system. Issue 9 (25th August 2014) - Yamamoto, Seiichi; Hamamura, Fuka; Watabe, Tadashi; Ikeda, Hayato; Kanai, Yasukazu; Watabe, Hiroshi; Kato, Katsuhiko; Ogata, Yoshimune; Hatazawa, Jun
Abstract : Purpose: : Cerenkov‐light imaging is a new molecular imaging technology that detects visible photons from high‐speed electrons using a high sensitivity optical camera. However, the merit of Cerenkov‐light imaging remains unclear. If a PET/Cerenkov‐light hybrid imaging system were developed, the merit of Cerenkov‐light imaging would be clarified by directly comparing these two imaging modalities. Methods: : The authors developed and tested a PET/Cerenkov‐light hybrid imaging system that consists of a dual‐head PET system, a reflection mirror located above the subject, and a high sensitivity charge coupled device (CCD) camera. The authors installed these systems inside a black box for imaging the Cerenkov‐light. The dual‐head PET system employed a 1.2 × 1.2 × 10 mm 3 GSO arranged in a 33 × 33 matrix that was optically coupled to a position sensitive photomultiplier tube to form a GSO block detector. The authors arranged two GSO block detectors 10 cm apart and positioned the subject between them. The Cerenkov‐light above the subject is reflected by the mirror and changes its direction to the side of the PET system and is imaged by the high sensitivity CCD camera. Results: : The dual‐head PET system had a spatial resolution of ∼1.2 mm FWHM and sensitivity of ∼0.31% at the center of the FOV. The Cerenkov‐light imaging systemˈs spatial resolution was ∼275 μ m for a 22 Na point source. Using the combined PET/Cerenkov‐light hybrid imaging system, the authors successfully obtained fused images from simultaneously acquired images. The image distributions are sometimes different due to the light transmission and absorption in the body of the subject in the Cerenkov‐light images. In simultaneous imaging of rat, the authors found that 18 F‐FDG accumulation was observed mainly in the Harderian gland on the PET image, while the distribution of Cerenkov‐light was observed in the eyes. Conclusions: : The authors conclude that their developed PET/Cerenkov‐light hybrid imaging system is useful to evaluate the merits and the limitations of Cerenkov‐light imaging in molecular imaging research.